Att motivera och underlätta återbruk genom re-design - Lindman, Rebecca; Ljungberg, Elin (My University, 2019)
Summary Each year City of Gothenburg purchases large quantities of office furniture. Awareness of the environmental effects of consumption has resulted in an intranet website dedicated to finding new homes for furniture within City of Gothenburg. Kretslopp och vatten, a public administration of City of Gothenburg, found that some types of furniture were more difficult than others to relocate. An initiative to get around this issue, together with Miljöbron, became the start of this project. The project goal was to deliver instruction manuals for office furniture re-design, in order to rescue pieces from being discarded as junk. In order to increase the demand for reuse of furniture within City of Gothenburg, these manuals were intended to be available on their intranet. Another poject guideline was that the re-designed furniture should suit an activity based office. The project started off with a litterature study of office trends and activity based working environments and an analysis of the flow of furniture within City of Gothenburg. The intranet website for second hand furniture was analysed as well as relevant purchase statistics. Details about how a change of furniture could take place was gathered through interviews with employees. This resulted in three generalised types of office furniture: adjustable height corner desks, under desk drawers and system shelves. These were intended to undergo re-design in order to go with the current office trends. The chosen generalised furniture was the outset of the concepts for re-design. The concept creation included several idea generations and practical tests in order to ensure achievability. The practical tests brought essential knowledge of materials, tools and surrounding. Eventually three instruction manuals were constructed, one for each of the re-design concepts, on the basis of being easily understood and engaging. The purpose of the instruction manuals is to present the benefits of re-design to encourage people to reuse. Therefore, there is a page in each instruciton manual presenting financal and environmental benefits of the re-design. This thesis indicates the potential of reused furniture and the possibility to easily find a new purpose of use. Furthermore, the instruction manuals have potential to be used as graphic support during development of new re-design within City of Gothenburg.
Keywords: Produktion; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Annan teknik; Production; Sustainable Development; Innovation & Entrepreneurship; Other Engineering and Technologies